Association of serum uric acid Levels with metabolic syndromes in Korean adolescents - Seo, Young-Jun; Shim, Young Suk; Lee, Hae Sang; Hwang, Jin Soon (Frontiers in Endocrinology, 2023)
Introduction The study findings investigated uric acid reference values and their association with a cluster of cardiometabolic risk factors among adolescents using the Korea National Health and Nutrition Examination Survey (KNHANES). Methods A retrospective cross-sectional study was conducted using the KNHANES database from 2016 to 2018, involving a total of 2,462 participants aged between 10 and 18 years. Based on age- and sex-specific percentile curves for serum uric acid (SUA) levels from the KNHANES, we examined the correlation between cardiometabolic risk factors and serum uric acid levels. Results The percentile values of SUA varied with sex and age. In male subjects, SUA levels tended to increase from 10 to 14 years of age and plateaued after 14 years of age. Moreover, the overall uric acid level in females was found to be lower than that in males; the levels tended to increase at approximately 10 to 12 years old but were relatively consistent according to age. Mean uric acid levels increased according to obesity status in both males and females. However, correlation analysis revealed that SUA levels were associated with several metabolic risks even after adjusting for obesity. The detailed metabolic syndrome (MetS) components that were observed to be associated with an increase in uric acid levels were different between males and females, but overall, high uric acid levels increased MetS risk. Additionally, a significant increase in MetS-related odds ratio (OR) for components, including waist circumference (WC), triglyceride (TG) levels, and low high-density lipoprotein cholesterol (HDL-c), was observed. However, differences between sexes were apparent, with a more pronounced increase in OR based on SUA levels in girls. Discussion SUA levels were closely associated with MetS and its components, even in nonobese subjects. Therefore, high SUA levels in children and young adolescents should be closely monitored to prevent MetS.